ISLAMIC EDUCATION TEACHERS AS GUIDANCE AGENTS FOR ADOLESCENTS IN FACING THE DIGITAL PSYCHOSOCIAL CRISIS - Muhammad Syukur; Susanto Susanto (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The digital era has presented complex challenges for adolescents in the form of psychosocial crises that require serious attention from the education sector. This study aims to analyze the strategic role of Islamic Religious Education teachers as guiding agents for adolescents in facing digital psychosocial crises. The research method uses a qualitative approach with library studies focusing on relevant literature analysis. The results show that adolescents experience various forms of digital psychosocial crises such as digital addiction, cyberbullying, identity crisis, and FOMO which impact mental health, academic performance, and spiritual values. Islamic Religious Education teachers have multidimensional roles as educators, counselors, mentors, and spiritual guides who can provide holistic guidance. Effective guidance strategies include digital-based learning approaches with integration of Islamic values, personal Islamic counseling, and comprehensive programs involving Islamic values-based digital literacy. Program implementation requires synergistic collaboration between schools, families, and communities with systematic stages and continuous evaluation. Program success can be measured through improved adolescent mental health, strengthened spiritual values, and enhanced Islamic values-based digital literacy. This research contributes to developing adolescent guidance models in the digital era that integrate Islamic values with modern technological challenges